A Summary of N, P, and K Research with Sweet Corn in Florida: SL 326/CV235, rev. 7/2010 - Hochmuth, George; Hanlon, Ed (EDIS, 2010)
Revised! SL-326, a 15-page illustrated fact sheet by George Hochmuth and Ed Hanlon, summarizes the historical Florida research literature on nitrogen, phosphorus, and potassium fertilization of sweet corn. Includes references. Published by the UF Department of Soil and Water Science, July 2010. SL 326/CV235: A Summary of N, P, and K Research with Sweet Corn in Florida (ufl.edu)